Mites (Arachnida: Acari) associated with plants of family Myrtaceae from the Caatinga Domain, Brazil - Rodrigues, Jennifer K. [UNESP]; Furtado, Imeuda P.; Lofego, Antônio C. [UNESP] (Systematic and Applied Acarology Society, 2020)
The objective of the present study was to determine the mite fauna associated with Myrtaceae from Cariri, a microregion with peculiar climatic conditions in the center of the Caatinga Domain in northeastern Brazil. Samples were collected in eight municipalities in Cariri region. In each municipality, five collection sites equidistant at approximately 10 km were established. The sampling was carried out in two periods, rainy season (March to April 2013) and dry season (September to October 2013). A total of 3.831 mites distributed in 14 families, 39 genera and 46 species were recorded. The Phytoseiidae was the dominant predatory mite family with 11 species. The most common phytoseiid species was Euseius concordis (Chant), followed by Euseius citrifolius Demark & Muma and Euseius alatus De Leon. Among the phytophagous mites, two families were the most abundant: Tenuipalpidae and Tetranychidae. Our results indicated that Myrtaceae in Caatinga Domains hosts a considerable diversity of potentially important predatory mites for the control of phytophagous species.
Keywords: host plants; mite diversity; Myrtaceae; northeastern Brazil; semi-arid environment